Duplicate Download Finder: Boost Storage Efficiency in Minutes - Dr Thiyagarajan V S; Arjun Aadhith B S; Bharathvaj V; Bushra M; Dhanush Sri S; Harshitha P (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This project introduces Duplicate Finder Pro, a cross-platform application built using Flutter and BLoC architecture to efficiently detect and manage duplicate files on desktop and Android devices. The system employs a combination of file metadata filtering and SHA-256 checksum matching to ensure accurate detection, while asynchronous processing and database caching maintain optimal performance. Users can choose between full and quick scan modes, apply extension-based filtering, and monitor real-time scanning progress. To safeguard against accidental data loss, duplicates are first moved to a secure recycle bin, from which they can be reviewed and restored if needed. Featuring a modern Material Design 3 interface and platform-specific optimizations, Duplicate Finder Pro provides a safe, fast, and user-friendly solution for reclaiming storage space and improving file organization.